Cold-Stimulus Headache in Children and Adolescents - Ilaria Bonemazzi; Maria Federica Pelizza; Giulia Berti; Claudio Ancona; Margherita Nosadini; Stefano Sartori; Irene Toldo (Life, 2023)
The literature on cold-stimulus headache (CSH) is relatively sparse compared to other primary headache disorders and the studies on the pediatric population are very limited. This systematic review aims to analyze the evidence on CSH in children and adolescents focusing on epidemiology, clinical features, pathogenic mechanisms, and treatments. Our review included 25 studies, among which 9 papers include pediatric cases (4 pediatric samples, 5 mixed samples of children and adults). The aim of this work is to highlight the features of CSH in children and adolescents. In children, the prevalence of CSH is higher than in adults and it is not gender-specific. There is a relevant family history for CSH and the comorbidity with migraine is significant. The triggers and clinical features of CSH due to ingesting a cold stimulus in children overlap with those in adults. CSH due to external application of a cold stimulus (or to environmentally low temperatures) is not studied in children and adolescents. We describe in detail a new pediatric case of CSH triggered by low ambient temperatures; to the best of our knowledge, this represents the first description in the literature. In conclusion, CSH in children is probably underestimated and has peculiar features compared to adults; further studies are needed to better understand its clinical features and pathophysiology.